Situation of the profession of public librarian at the University of Majorca (1770-1808) - Longás Lacasa, Maria Ángeles (Revista General de Información y Documentación, 2016)
The University of Majorca receives in 1770, by royal donation, the libraries that the Jesuits had formed in their schools of Montesión and San Martin in Palma and San Ignacio in Pollença. The purpose of this work is to study the librarians who were in charge of this university and public library, formed by the union of the three mentioned libraries. All requests to King Carlos III sent from Mallorca to fill this position are also analyzed. The methodology has been the examination of the documentation generated in the period and preserved in historical archives of Madrid and Palma. The results of the research show that the library profession in Majorca, in the second half of the eighteenth century, has prestige and it is highly regarded by society.